D4.8 Material virtual training - Hadjimitsis, Diofantos G.; Nisantzi, Argyro; Themistocleous, Kyriacos; Mettas, Christodoulos; Evagorou, Evagoras G.; Agapiou, Athos; Lysandrou, Vasiliki; Papoutsa, Christiana; Christofe, Andreas; Tzouvaras, Marios; Lasaponara, Rosa; Masini, Nicola; et al. (My University, 2018)
Work package 4 focused on the training and knowledge transfer between the existing personnel of the Remote Sensing Lab of the Cyprus University of Technology and experts from the high performing partners’ institutions. The current deliverable consists precisely of the specific training/knowledge transfer activity of the virtual trainings that have took place throughout the project. The deliverable provides a brief description for each virtual training, all relative information as per topic, participants, date etc. Also, the material produced by each trainer, is also hereunder displayed. The topics of virtual trainings focused on the analysis of hyperspectral images, the use of remote sensing for looting monitoring and the multi-temporal remote sensing analyses. In addition, the fourth virtual training was focused on the Integration of RS data for Cultural Heritage management in the Copernicus Era.
Keywords: Knowledge transfer; Virtual training; Hyperspectral images; Remote sensing; Cultural heritage